ANALISIS STAKEHOLDER DALAM IMPLEMENTASI KEBIJAKAN KOTA LAYAK ANAK (KLA) DI KOTA BANDAR LAMPUNG STUDI PADA KLASTER PERLINDUNGAN KHUSUS - Sahisnu, Ayyas Alfath; Meutia, Intan Fitri; Prihantika, Ita (Jurnal Administrative Reform, 2025)
The government is facing serious challenges related to the increasing problem of violence against children. To overcome this problem, the government has taken active steps and various efforts have been made so that the issue of child violence can be addressed holistically. One of them is the existence of a Child Friendly City policy especially for protection clusters. Therefore, this research aims to analyze the interests and influence of stakeholders in implementing the Child Friendly City policy in the study of the Special Protection Cluster in Bandar Lampung City. The method used is a quantitative approach with descriptive statistics. Data analysis was carried out through stages according to Reed et al. (2009). The research results show that the stakeholders included in the key player category consist of the Bandar Lampung City Women's Empowerment and Child Protection Service (PPPA Service), the Bandar Lampung City Social Service, the Bandar Lampung City High Court, and the Bandar Lampung City High Prosecutor's Office. Stakeholders in the subject category consist of the Regional Children's Forum (FAD). Stakeholders in the context setter category are the Bandar Lampung City Regional Police, the Bandar Lampung City Law and Human Rights Regional Office, and the Bandar Lampung City Manpower and Transmigration Service. and stakeholders included in the crowd category are the Bandar Lampung City Education and Culture Office, the Bandar Lampung City Health Service. Collaborative implementation is very necessary to ensure equal distribution of benefits and responsibilities fairly to all stakeholders.